A robust and modular synthesis of ynamides. Issue 16 (6th November 2014) - Mansfield, Steven J.; Campbell, Craig D.; Jones, Michael W.; Anderson, Edward A.
Abstract : A flexible, modular ynamide synthesis is reported that uses a wide range of amides and electrophiles, including acyclic carbamates, hindered sulfonamides, and aryl amides. Abstract : A flexible, modular ynamide synthesis is reported that uses trichloroethene as an inexpensive two carbon synthon. A wide range of amides and electrophiles can be converted to the corresponding ynamides, importantly including acyclic carbamates, hindered amides, and aryl amides. This method thus overcomes many of the limitations of other approaches to this useful functionality.